The Efectivenees of Classical Music Therapy Concerning the Language Ability on Sekolah Kebutuhan Khusus Denpasar, years 2012 - Ida Ayu Herna Kusuma Wulandari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
The number of autism in the world is dramatically increased. The cause of autism is surely not known yet. The symptom that emerge from the child that suffering autism is there is a trouble in social interaction development, communication and behavior that can be detected by inspection by using the chat, checklist from ICD-10 and DSM-IV. Meanwhile, one of the solutions in non pharmacological is by classical music therapy. The purpose of this study is to know how far the effectively of the classical music to language ability of the child suffered autism. The research is by using pre-experimental design with one group pretest-posttest design. The sample composing 10 chosen person by using purposive sampling method. The data analysis by observation and measure with language ability test using Massey Language Ability Test. The research result after using classical music therapy is find in observation page (1,2,3,7) is decrease after pre-test result for all of the children, and in observation page 4,5,6 there is an improvement of six children and two children have a same point, and language ability test is improvement of all children. The classical music therapy give an effect to improve language ability in child that suffered autism. The statistic test in use is Wilcoxon Paired t-Test (p<0,05). After the data analyst, result that found is the classical music therapy have an effect to improve language ability of the child that suffered autism. Based on previous result, it is suggested to the therapist to always using this Classical Music Therapy as alternative therapy in the process of learning. To the next researcher to analysis about the time period that is precise in use this classical music therapy and with larger samples then the previous one.